2022
DOI: 10.1080/10717544.2022.2058653
|View full text |Cite
|
Sign up to set email alerts
|

Sonosensitizer nanoplatform-mediated sonodynamic therapy induced immunogenic cell death and tumor immune microenvironment variation

Abstract: Epithelial ovarian cancer (EOC) is one of the most lethal gynecologic malignancies, and effective treatments are still lacking due to drug tolerance and tumor recurrence. In this study, we aimed to investigate the effects of sonodynamic therapy (SDT) on ovarian cancer and its potential mechanism. Folate receptor-targeted and ultrasound-responsive nanoparticles (NPs) were constructed using PLGA-PEG-FA (PLGA: poly (lactic-co-glycolic) acid, polyethylene glycol (PEG), FA: folate), the reactive oxygen species (ROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…And these keywords with an ongoing burst until now deserve special attention because they may have great potential to continue to be hot topics in the near future ( Wu et al, 2021a ). Taken together with keywords co-occurrence and burst analysis, with the exception of nanomaterials-related studies including nanoparticles, mesoporous silica nanoparticles, nanosheets, liposomes, microbubble and TiO 2 nanoparticle, the following research directions such as immunogenic cell death ( Zheng et al, 2021 ; Zheng et al, 2022 ), metal-organic framework ( Pan et al, 2018b ), photothermal therapy ( Liang et al, 2019 ), hypoxia ( Chen et al, 2017 ; Zhu et al, 2018 ), tumor microenvironment ( An et al, 2020 ), chemodynamic therapy ( Bai et al, 2020 ), combination therapy ( Ning et al, 2022 ), tumor resistance ( Guan et al, 2022 ), intensity focused ultrasound ( Ohmura et al, 2011 ; Roberts et al, 2022 ), drug delivery ( Ren et al, 2022 ), and Staphylococcus aureus ( Yu et al, 2021 ) also deserve further attention and may continue to explode in the future. Given space limitations, we only discussed several directions such as immunogenic cell death (ICD), hypoxia and Staphylococcus aureus as follows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And these keywords with an ongoing burst until now deserve special attention because they may have great potential to continue to be hot topics in the near future ( Wu et al, 2021a ). Taken together with keywords co-occurrence and burst analysis, with the exception of nanomaterials-related studies including nanoparticles, mesoporous silica nanoparticles, nanosheets, liposomes, microbubble and TiO 2 nanoparticle, the following research directions such as immunogenic cell death ( Zheng et al, 2021 ; Zheng et al, 2022 ), metal-organic framework ( Pan et al, 2018b ), photothermal therapy ( Liang et al, 2019 ), hypoxia ( Chen et al, 2017 ; Zhu et al, 2018 ), tumor microenvironment ( An et al, 2020 ), chemodynamic therapy ( Bai et al, 2020 ), combination therapy ( Ning et al, 2022 ), tumor resistance ( Guan et al, 2022 ), intensity focused ultrasound ( Ohmura et al, 2011 ; Roberts et al, 2022 ), drug delivery ( Ren et al, 2022 ), and Staphylococcus aureus ( Yu et al, 2021 ) also deserve further attention and may continue to explode in the future. Given space limitations, we only discussed several directions such as immunogenic cell death (ICD), hypoxia and Staphylococcus aureus as follows.…”
Section: Discussionmentioning
confidence: 99%
“…ICD is a particular modality of cell death characterized by the upregulation of various damage-associated molecular patterns (DAMPs), and generally be triggered by several chemotherapeutic agents such as oxaliplatin, anthracyclines, and paclitaxel ( Kroemer et al, 2022 ). Increasing studies have found that SDT is capable of inducing ICD in multiple cancer types and promises to play an assistive role in tumor immunotherapy ( Zheng et al, 2021 ; Zheng et al, 2022 ). For example, Wan and colleagues have designed a nuclear-targeting delivery system TIR@siRNA to achieve the gene augmented nuclear-targeting SDT.…”
Section: Discussionmentioning
confidence: 99%
“…B. bidum activated ROS during proliferating, which can alleviate certain cancers and promote tumor apoptosis and death, and accelerate autophagy through different pathways. 16,24,29 The morphological changes of tumor cells under an electron microscope might be direct evidence. The adsorption of B. bidum and classic enhanced permeability and retention (EPR) The HE staining results indicated that the tumor tissue in the B. bidum@CL-PFH-DOX-NPs + PFUS group had more severe damage, including nuclear fragmentation, dissolution, liquefaction, and vacuolization in the cytoplasm, even complete disappearance of cell structure, which was similar to the results by Wang et al 2 The apoptosis phenomenon was also notable in the B. bidum@CL-PFH-DOX-NPs + PFUS group compared with controls, suggesting a higher tumor-killing effect than that of B. bidum combined with PFUS or CL-PFH-DOX-NPs combined with PFUS.…”
Section: Discussionmentioning
confidence: 99%
“…PFH is capable of liquid-gas phase transition and is oen used for enhancing imaging and improving the cavitation effect of ultrasound. 16,17 DOX is one of the most widely studied and used adjuvant antitumor drugs in clinical practice, 18 and has a broadspectrum full-cycle inhibitory effect on tumor cells. 19 Based on the above-mentioned research ndings, we propose a new strategy to comprehensively improve the efficacy of tumor treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[62] In vitro experiments revealed that TiO 2 -Ce6-CpG showed an efficient internalization into the cells (Figure 7c). After various experimental analysis, it was found that CD11c and CD86 as the representative markers of DCs maturation were up-regulated, Enhanced SDT and immune response stimulation [62] Mn-MOF Mn-MOF 4T1 Cyclooxygenase activity rise and GSH content drop [88] sPD-1/Ce6-NBs Ce6, NBs HCC Induced UTND, enhanced SDT and immune response [89] RBC-mTNPs@AQ4N mTNPs, AQ4N, RBC MCF-7 Immune escape, hypoxia activation chemotherapy [63] THPP-Oxa(IV)-PEG THPP, Oxa(IV)SA 2 , PEG 5k -COOH CT26 Immunogenic nanodrug and radioisotope imaging [90] PIH-NO HSA-NO, FDC, IR780 4T1 Mitochondrial damage, drug accumulation, and M2 macrophage polarization into M1 phenotypes [91] LiP-PFH DPPC, DSPC, DSPE-PEG2000 4T1 Enhanced anti-tumor immunity [92] OI_NPs OXP, ICG, PFP ID8 Improved optical and ultrasonic imaging [93] FA-MnPs MNP, FA TNBC M2 macrophages polarized to M1 phenotype, ICD response to activate NK, DC maturation [94] RSL3@O 2 -ICG NBS NBS, ICG, RSL3 HCC Ferroptosis [87] SnNSs@PEG 2D SnNS, PEG H1299 Excellent photothermal efficiency [64] MPN-PALF LOX, ATO, Ce6 4T1 Relieving acidic TME [95] MG@PNPs PMnC, Gox 4T1 MR/PA dual-mode imaging and tumor starvation treatment [96] 𝛼-Fe 2 O 3 @Pt 𝛼-Fe 2 O 3 , Pt 4T1 Inhibiting electron-hole pairs recombination for ROS production [97] P/M@CasMTH1 MOF, CRISPR-Cas9, MTH1 A549 Controlled release and enhanced SDT [86] MitoCAT-g CAT-g, CA, TPP HCC GSH exhaustion [84] Wettability of nanoparticles MSN, PSS Thrombus Enhanced SDT [59] FA-N-GQds FA, N-GQD, pyridine N, pyrrole N MDA-MB-231 High tumor labeling rate [61] ZIF-8 NCS ZIF-8, MOF 4T1 Acidic TME modulation [80] IRO@FANP PLGA, PEG, FA ID8 Enhanced SDT [98] IR820@NCP IR820, FTS HCC Tumor aggregation and fluorescence imaging [99] Pd/H-TiO 2 NSS Pd, NSS C6 Enhanced CDT and SDT [100] indicating that nanosonosensitizer TiO 2 -Ce6-CpG could significantly promote DCs maturation in vitro. In the in vivo experiment of female C57BL/6 mice inoculated with Hepa1-6, it was found that the treatment with such composite sonosensitizers (TiO 2 -Ce6-CpG) combination with PD-L1 inhibitor could not only effectively inhibit the primary tumor but also significantly delay the growth of distant tumors (Figure…”
Section: Nanobiotechnology-augmented Sdt In Combination With Immunoth...mentioning
confidence: 99%